THE IMPACT OF ADVANCED COMPUTER HARDWARE ON STUDENT LEARNING OUTCOMES IN VIRTUAL LEARNING ENVIRONMENTS IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
The rapid evolution of digital technologies has transformed educational delivery, particularly in virtual learning environments (VLEs). This study investigates the impact of advanced computer hardware on student learning outcomes in VLEs within Cross River State, Nigeria. Utilizing a quantitative approach, data were collected through structured questionnaires from 548 secondary school students across 11 schools in Akamkpa Local Government Area during the 2023/2024 academic session. The findings reveal that advanced hardware, such as high-speed processors and increased RAM, significantly enhances student engagement, academic performance, and digital literacy, with a statistically significant positive correlation (r = 0.62, p < 0.05). However, challenges like poor internet connectivity and limited hardware access in rural areas hinder optimal outcomes. Demographic analysis indicates equitable benefits across gender but disparities based on socioeconomic status. The study underscores the need for infrastructural improvements and equitable resource distribution to maximize the potential of advanced hardware in VLEs. Recommendations include government investment in ICT infrastructure and teacher training to optimize technology integration. This research contributes to the discourse on digital transformation in education, particularly in developing contexts.